Instructional Communication Model Of Military Education As An Effort To Achieve Center Of Excellence (Case Study: Akmil Magelang) - Kholil, Kholil; Santoso, Totok Imam; Widaningsih, Titi; Widowati, Dewi (Advances in Social Sciences Research Journal, 2022)
Communication is one of the important elements that play a role in shaping the interaction between educators and students. The change in the Indonesian Military Academy (Akmil) education curriculum in 2009 was one of the most significant changes, in which students received an academic education equivalent to a bachelor's qualification. However, in its application the education system has not been maximized to allow students to become experts both in the military and academic fields. The objectives of this study are, firstly, to identify and analyze the role of educators in the educational communication process in the Akmil to produce quality graduates; second, to design appropriate communication patterns between educators and students; and third, to build an educational communication model in the Akmil as a Center of Excellence, so that they are able to answer the challenges of the task in accordance with the changes and demands of the times. By using a mixed method with an exploratory sequential model, the research explores information by conducting in-depth interviews with 9 informants, both practitioners and academics, and distributing questionnaires to 145 cadets. The results show that there are still difficulties in applying the principle of 'completion of orders', where a command can be given with better rationality. To that end, the researcher then completed the findings, by formulating an instructional communication model through the Strategic Assumptions Surfacing and Testing (SAST) and Analytical Hierarchy Process (AHP) methods. As a result, this model puts an emphasis on the role of the Academic Gadik actor, which creates interactivity and communication intensity for the cadets. With this model, it is hoped that the Akmil will become a Center of Excellence for the military with high rational abilities.